The study of history based on local antiquity: A case study of existence of Kampar River in analyzing the past maritime in teaching history - Kamaruddin, Kamaruddin; Ahmal, Ahmal (FKIP-Universitas Riau, 2018)
This paper describes the history-based learning local history,which takes the case of the existence of the Kampar River as local aspects inthe learning of the maritime history in Indonesia. The data obtained throughthe triangulation by collecting interviews, observation, documentation studyand refered to articles, journals, textbooks and data other documents in thelibrary that supported the teaching of history based on local history in theanalyzing of maritime history in Indonesia, then it was investigated anddrawn as a conclusion that the Kampar River was able to be used as thestudy of history in the local context in understanding of the teaching historyin Indonesia related to maritime history. The results in this study show thatfirst, Kampar River is a river that is loaded with historical events of theKingdom of Sriwijaya, The Kingdom of Islamic until the independence ofIndonesia. Second, the existence of Kampar River as a aspect of emergenceof history / local aspect which is able to be used as information about themaritime historyto the learners. For learning process, it involves localaspects of learners to connect, internalize and develop cooperation inanalyzing of the concept aspects practicely in teaching maritime history. Theconcept of local history-based teaching history is contextually-learninglearning concept that emphasizes the relevance of teaching materials withreal world of learners. The existence of Kampar River is a means emergenceof history / local aspect can be used as information about the maritimehistory to assist in the understanding of teaching maritime history on thelearner, for learning involving local aspects for learners to connect,internalize and develop cooperation in analyzing aspects of the concept topraxis in teaching maritime history. The concept of local history-basedteaching history is contextually-learning learning concept that emphasizesthe relevance of teaching materials with real world of learners. The existenceof Kampar River is a means emergence of history / local aspect can be usedas information about the maritime history to assist in the understanding ofteaching maritime history on the learner, for learning involving local aspectsfor learners to connect, internalize and develop cooperation in analyzingaspects of the concept practically in learning the maritime history. Theconcept of local history-based learning is contextually-learning thatemphasizes the relevance of teaching materials with real world of learners.